Sports management and level of teaching performance in teachers of Physical education - Castro Pérez, Carla (2020)
This research was made to define the relationship between the variables sports management and teaching performance in Physical Education teachers at UGEL 07 in Lima Metropolitana, 2019. It was developed within the quantitative approach, based on the correlational-descriptive design and cross section. The sample included 50 Physical Education teachers from the mentioned entity. The surveys and the data collection sheet allowed verifying that there is a relationship between the variables. It was concluded that there is a direct, linear and significant relationship between sports management and teaching performance. Furthermore, there is the same level of relationship between the organizational dimensions and collegial coordination. With these contributions, a strategy will be created that seeks to strengthen the sports management of teachers and better understand its implication in the pedagogical role.